Incorporation of single cobalt active sites onto N-doped graphene for superior conductive membranes in electrochemical filtration - Pan, Meilan (2022)
The employment of electrochemical technology in membrane filtration promises high separation efficiency with minimal membrane fouling. Herein, we fabricated single cobalt atom and nitrogen atom codoped graphene (NG-Co) as a conductive membrane, and showed that it achieved 99.5% rejection at a small voltage of 2.5 V and exhibited excellent reusability. The turnover frequency of the single Co site was about 13.5 times larger than that of traditional Co-based nanocatalysts, because the single Co site served as the key electrochemical active site to degrade the organic pollutants, while the nitrogen-doped groups of graphene served as efficient binding sites for the immobilization of the single Co site to improve the intrinsic catalytic activity of the Co sites. This study has important implications for the design of graphene-based conductive membranes in the electrochemical remediation of wastewater.